Atrial arrhythmias related to antitumor treatment in patients with coronary heart disease and malignant tumors - Zhang, Beibei; Zhang, Lei; Ren, Yili; Xu, Chenkai (Frontiers in Oncology, 2025)
AimsThis study investigated the occurrence of arrhythmias in patients with malignant tumors and coronary heart disease (CHD) during antitumor drug treatment.Methods109 patients with malignant tumors undergoing antitumor treatment at Zhejiang Hospital from January 2023 to January 2024 were analyzed. All patients underwent 12-lead ECG before and after each chemotherapy cycle. The primary endpoint was the occurrence of new arrhythmias recorded through ECG. Univariate and multivariate logistic regression analysis were performed to recognize the risk factors.ResultsAtrial arrhythmias occurred in 13 cases (11.93%). The incidence of atrial arrhythmias was significantly higher in the CHD group compared to the non-CHD group (27.27% vs 1.54%; P < 0.001). Multivariate logistic regression analysis indicated that smoking (P = 0.009), ischemic heart disease (P = 0.006), and left ventricular ejection fraction < 50% (P = 0.014) increased the risk of developing arrhythmias after antitumor treatment.ConclusionAtrial arrhythmias are more common in cancer patients with CHD when undergoing antitumor treatment. A history of smoking, ischemic heart disease, and reduced left ventricular ejection fraction increases the risk of atrial arrhythmias after antitumor therapy.